La territorialisation olympique - Egidio Dansero; Alfredo Mela (Revue de Géographie Alpine)
Mega-events, as the Olympic Games, receive an increasing attention in the debate about urban transformations. They have multiple dimensions but surely one of the most important impacts are the spatial ones. They are an occasion of extraordinary urban transformation, in its inside structure, in its image and in its external competitiveness. Moving from Torino 2006, this paper present a theoretical approach to study the territorialization of mega-events and the problematic challenge of the legacy.